RANCANG BANGUN SISTEM INFORMASI PEMBAYARAN SPP DI POLITEKNIK HASNUR DENGAN MENGGUNAKAN FRAMEWORK CODEIGNITER 3 - Ainun Jariah; Abdullah Ardi (Program Studi Teknik Informatika, Politeknik Hasnur, 2021)
The tuition fee payment system is a mechanism for transferring funds charged to students for educational institutions to expedite the lecture process in terms of learning and teaching. Design of an SPP Payment Information System at Hasnur Polytechnic Using the Codeigniter 3 Framework was created using the programming language PHP, codeigniter framework 3 and database MySQL. This application was made in order to facilitate the financial section for managing payment data and students can find out the tuition payments they have made and will be paid. The research method uses a waterfall from the analysis stage to application testing. Then the system design is carried out using DFD (Data Flow Diagram) and design is interface also done at this stage. Furthermore, writing the program code is done using the PHP programming language and the codeigniter framework. Then the results of the study were tested using the method black box testing. The test results state that the program is in accordance with the described functional require.